THE USE OF COOKING VIDEO BY “MASTERCHEF CANADA” TO IMPROVE STUDENTS’ WRITING ABILITY OF PROCEDURE TEXT AT THE TENTH GRADE STUDENTS SMAN 1 GROBOGAN - Rio Septa Ardhana; A.B. Prabowo K.A; Tarcisia Sri Suwarti (Melati Institute, 2023)
This research conducted the use of cooking video by “MasterChef Canada” to improve students’ writing ability of procedure texts. The purpose of the study were 1) to find out the students’ writing ability in procedure text without using cooking video by “MasterChef Canada”. 2) to find out the students’ writing ability in procedure text using cooking video by “MasterChef Canada”. 3) to find out the significant difference of the students’ writing ability in procedure text between students who were taught without using cooking video by “MasterChef Canada” and students who were taught using cooking video by “MasterChef Canada”. The researcher conducted quantitative research, the design of this research was true-experimental design with a pre-test post-test control group design. The sample of this research was 68 students at tenth-grade students of SMAN 1 Grobogan consisting of experimental class and control class. The instrument of this research is a test, namely pre-test and post-test. The data were analyzed using SPSS Version 21. Based on the result, the mean score of pre-test was 60.56. And the mean score of post-test was 81.50. The use of Cooking Video by “MasterChef Canada” effective to improving student writing ability in procedure text as indicated by the t-test value 7.031 and the p-value (2-tailed) .000 which was not greater than .05 level of significant. It means that using Cooking Video by “MasterChef Canada” as teaching media had significant effect in students’ learning writing in procedure text.